Influence of wettability on water-oil two-phase flow in three-dimensional porous media based on level set method - FU Hongtao; SONG Kaoping; ZHAO Yu; DING Chao; LIANG Lihao; ZHANG Jian (Youqi dizhi yu caishoulu)
Water flooding is one of the most important methods for reservoir development. Water flooding production contributes to over 70% of crude oil production in China. The wettability of rock surfaces is a key factor influencing the water-oil two-phase flow process and the microscopic displacement efficiency in the porous media of reservoirs. A micropore structure model of sandstone was established using computed tomography （CT） scanning technology to elucidate the influence of wettability on the flow behavior of water-oil two-phase in three-dimensional porous media. Based on Navier-Stokes equations， the immiscible flow of water-oil two-phase in microscopic three-dimensional porous media was simulated， and the level set （LS） method was used to capture the interface changes of the two-phase in real time. The results show that wettability significantly influences the microscopic displacement efficiency， fluid distribution， and flow paths of water flooding in three-dimensional porous media. When the rock surface is in a water-wet state， the injected water can rapidly mobilize and uncover the oil droplets of the porous medium. In an oil-wet state， the water tends to flow readily along the central positions of pore throats， forming film-like remaining oil. The water-oil interface is mainly affected by capillary force， viscous force， and displacement pressure in water-wet or oil-wet pore throats. Wettability and pore throat diameter affect the direction of various forces. Moderately adjusting the wettability of rock surfaces will delay the occurrence of the water flooding fingering phenomenon and enhance the microscopic displacement efficiency.